A small mission concept to the Sun–Earth Lagrangian L5 point for innovative solar, heliospheric and space weather science. (August 2016) - Lavraud, B.; Liu, Y.; Segura, K.; He, J.; Qin, G.; Temmer, M.; Vial, J.-C.; Xiong, M.; Davies, J.A.; Rouillard, A.P.; Pinto, R.; Auchère, F.; et al.
Abstract: We present a concept for a small mission to the Sun–Earth Lagrangian L5 point for innovative solar, heliospheric and space weather science. The proposed INvestigation of Solar-Terrestrial Activity aNd Transients (INSTANT) mission is designed to identify how solar coronal magnetic fields drive eruptions, mass transport and particle acceleration that impact the Earth and the heliosphere. INSTANT is the first mission designed to (1) obtain measurements of coronal magnetic fields from space and (2) determine coronal mass ejection (CME) kinematics with unparalleled accuracy. Thanks to innovative instrumentation at a vantage point that provides the most suitable perspective view of the Sun–Earth system, INSTANT would uniquely track the whole chain of fundamental processes driving space weather at Earth. We present the science requirements, payload and mission profile that fulfill ambitious science objectives within small mission programmatic boundary conditions. Highlights: A small mission concept to the Sun–Earth Lagrangian L5 point is proposed. The mission tackles new science objectives with innovative instrumentation. A full mission design consistent with small mission constraints is described.